What do student jobs on graduate CVs signal to employers? - Eva Van Belle; Ralf Caers; Laure Cuypers; Marijke De Couck; Brecht Neyt; Hannah Van Borm; Stijn Baert (Global Labor Organization (GLO), 2019)
Due to the prevalence and important consequences of student work, the topic has seen an increased interest in the literature. However, to date the focus has been solely on measuring the effect of student employment on later labour market outcomes, relying on signalling theory to explain the observed effects. In the current study, we go beyond measuring the effect of student work and we examine for the first time what exactly is being signalled by student employment. We do this by means of a vignette experiment in which we ask 242 human resource professionals to evaluate a set of five fictitious profiles. Whereas all types of student work signal a better work attitude, a larger social network, a greater sense of responsibility, an increased motivation, and more maturity, only student employment in line with a job candidate's field of study is a signal of increased human capital and increased trainability.
Keywords: C91; I21; J22; J24; 330; Student employment; signalling; hiring chances; vignette study